Inhaled silica nanoparticles exacerbate atherosclerosis through skewing macrophage polarization towards M1 phenotype - Stachyra, Kamila; Wiśniewska, Anna; Kiepura, Anna; Kuś, Katarzyna; Rolski, Filip; Czepiel, Klaudia; Chmura, Łukasz; Majka, Grzegorz; Surmiak, Marcin; Polaczek, Justyna; van Eldik, Rudi; Suski, Maciej; et al. (Ecotoxicology and Environmental Safety, 2022)
Background and aims: Exposure to environmental nanoparticles is related to the adverse impact on health, including cardiovascular system. Various forms of nanoparticles have been reported to interact with endothelium and induce inflammation. However, the potential role of nanoparticles in the pathogenesis of atherosclerosis and their mechanisms of action are still unclear. The aim of this study was to investigate the effect of two broadly used nanomaterials, which also occur in natural environment - silicon oxide (SiO2) and ferric oxide (Fe2O3) in the form of nanoparticles (NPs) - on the development of atherosclerosis. Methods: We used apolipoprotein E-knockout mice exposed to silica and ferric oxide nanoparticles in a whole body inhalation chamber. Results: Inhaled silica nanoparticles augmented the atherosclerotic lesions and increased the percentage of pro-inflammatory M1 macrophages in both the plaque and the peritoneum in apoE-/- mice. Exposure to ferric oxide nanoparticles did not enhance atherogenesis process, however, it caused significant changes in the atherosclerotic plaque composition (elevated content of CD68-positive macrophages and enlarged necrotic core accompanied by the decreased level of M1 macrophages). Both silica and ferric oxide NPs altered the phenotype of T lymphocytes in the spleen by promoting polarization towards Th17 cells. Conclusions: Exposure to silica and ferric oxide nanoparticles exerts impact on atherosclerosis development and plaque composition. Pro-atherogenic abilities of silica nanoparticles are associated with activation of pro-inflammatory macrophages.
CRIS-Team Scopus Importer:2022-01-07
Keywords: ApoE-knockout mice; Atherosclerosis; Atherosclerotic plaque; Macrophages; Nanoparticles